ORIENTALISME ANTARA LAWAN DAN KAWAN: Telaah Historis Transformasi Perkembangan Orientalisme, Imperialisme, dan Evangelisme - Luthfan, Muhammad Aqil (Kopertais Wilayah X Jawa Tengah, 2013)
AbstractThis paper seeks to explore whether such construction was behind the emergence of the phenomenon of orientalism, imperialism and evangelicalism. To examine the historical correlation, while reconstructing the new identity of Islam and Western civilization. Thoose phenomenons are analyzed in this paper to see the diachronic development objectively and comprehensively. From this it can be concluded that Tulian Orientalism transformed form of movement imperilisme Western and Christian missionarisme phisical-material nature, become more institutionalized academic topics and tend menginggalkan roots of its emergence. Awareness of this transformation is expected to open dialogue between the parties in a cooperative effort towards the interests of a better humanity.Kata Kunci: orientalisme, imperialisme dan evangelism